The Influence of Country of Origin Cues on Product Evaluation: Evidence from Swiss and German Consumers (2017)
This study aimed to investigate the influence of visual symbols on the perception and evaluation of two fictitious products as well as the effect of demographic characteristics (nationality) on consumers’ evaluations. A sample of 373 participants was split into two groups and two experimental conditions (products with Swiss symbols and products without Swiss symbols). One group of participants rated the packaging without a Swiss flag and the other one rated the same packaging with a Swiss flag. A semantic differential scale and the Self-Assessment Manikin (SAM) were used to assess attitudes toward the products. Results confirm that there are differences between the two independent groups and that nationality has an effect on product perception and evaluation. Visual symbols such as a country flag can lead to a better product perception and evaluation. Finally, implications for research are discussed.